P PENGALAMAN PERAWAT YANG PERNAH TERKONFIRMASI COVID-19 DI RSUD SULTAN SURIANSYAH - Sri Sundari; Lukman Harun (Journal of Nursing Invention, 2021)
Background:The high incidence of COVID-19 which causes a pandemic for the whole world, even Indonesia, South Kalimantan have quite large numbers related to the COVID-19 disease, one of which is health workers, one of which is a nurse, nurses are people who improve alot of things. interact with patients in hospitals, so that nurses are also quite a lot infected or confirmed COVID-19.Objective:to obtain an overview of the experiences of nurses who have been confirmed by COVID-19 at the Sultan Suriansyah Hospital.Method:used in this study is a qualitative method with a phenomenological design. Data collection was carried out by exploring ten participants. Data collection was carried out by in-depth interviews with ten nurses who had confirmed COVID-19 at the Sultan Suriansyah Hospital. Data analysis using Collaizzi's technique. Results:namely: (1) understanding of COVID-19; (2) signs of symptoms of COVID-19 (3) the process of transmission of COVID-19; (4) Establishing a Confirmed Diagnosis of COVID-19; (5) the body's response after knowing that COVID-19 is confirmed; (6) Actions after knowing that COVID-19 is confirmed; (7) Hope after being declared cured. Conclusion: The nurse's experience in this study was a disease caused by the corona virus which affected the respiratory system, digestion, discomfort and the human body's immune system, which quickly transmitted to others, thus requiring us to maintain health protocols. To pay more attention to health protocols both at home and in the hospital.